Dr. Seuss's Horton hears a Who pop-up! - Geisel, Theodor Seuss Dr. 1904-1991.; Carter, David A.; Gerardi, Jan (New York : Random House, 1991)
Horton finds an entire city of Whos on a speck of dust, but, since no one else can see them, no one believes they exist.
K
Includes five full-page pop-up illustrations, eleven pop-up booklets, movable pieces, etc.
b
b
Keywords: Elephants -- Juvenile fiction; Pop-up books -- Specimens; Stories in rhyme; Elephants -- Fiction; Pop-up books; Toy and movable books; Elephants -- Fiction; Stories in rhyme; Fantasy fiction; Toy and movable books